Evolution of Hair Treatment and Care: Prospects of Nanotube-Based Formulations - Santos, Ana Cláudia (2019)
A new approach for hair treatment through coating with nanotubes loaded with drugs or dyes for coloring is suggested. This coating is produced by nanotube self-assembly, resulting in stable 2-3 µm thick layers. For medical treatment such formulations allow for sustained long-lasting drug delivery directly on the hair surface, also enhanced in the cuticle openings. For coloring, this process allows avoiding a direct hair contact with dye encased inside the clay nanotubes and provides a possibility to load water insoluble dyes from an organic solvent, store the formulation for a long time in dried form, and then apply to hair as an aqueous nanotube suspension. The described technique works with human and other mammal hairs and halloysite nanoclay coating is resilient against multiple shampoo washing. The most promising, halloysite tubule clay, is a biocompatible natural material which may be loaded with basic red, blue, and yellow dyes for optimized hair color, and also with drugs (e.g., antilice care-permethrin) to enhance the treatment efficiency with sustained release. This functionalized nanotube coating may have applications in human medical and beauty formulations, as well as veterinary applications.